Systematic multi-level optimization design and dynamic control of less-rare-earth hybrid permanent magnet motor for all-climatic electric vehicles. (1st November 2019) - Zhu, Xiaoyong; Fan, Deyang; Xiang, Zixuan; Quan, Li; Hua, Wei; Cheng, Ming
Highlights: Systematic optimization design and dynamic control are established for EVs. Comprehensive optimization of less-rare-earth PM motor is carried out. MOGA and RS method are both employed to realize the optimal motor design. Resonance compensation method is utilized to suppress torque and speed vibration. A motor test platform is built to verify proposed optimization strategy and motor. Abstract: Motors that convert electrical energy to mechanical energy, have been considered as one of the most crucial components of all-climatic electric vehicles (EVs). In order to realize high-quality energy conversion, motor optimization has attracted considerable attention in the research field of motors. In this paper, systematic multi-level optimization design and dynamic control strategy is proposed for a less-rare-earth hybrid permanent magnet (LRE-HPM) motor. In the proposed systematic optimization strategy, the design requirements of the motor design level and control level are considered comprehensively. In the motor design level, the comprehensive sensitivity analysis is adopted to stratify design parameters, and the response surface method and multi-objective genetic algorithm are implemented respectively. In the motor control level, the resonance compensation strategy is established to further suppress torque ripple and speed vibration. Finally, a prototype motor is built and tested. Both simulation and experimental results not only verify the effectiveness of the proposed systematic optimization and dynamic control strategy, but also offer a research orientation for realizing high-quality energy conversion of all-climatic EVs.